Real Clinical Practice Register of Albuminuria Detection in Patients with Previously Undiagnosed Chronic Kidney Disease - A. G. Arutyunov; M. M. Batyushin; G. P. Arutyunov; M. Yu. Lopatin; E. I. Tarlovskaya; A. I. Chesnikova; S. V. Nedogoda; A. S. Galyavich; D. S. Tokmin; T. I. Batluk; R. A. Bashkinov; E. D. Gordeychuk; et al. (Архивъ внутренней медицины, 2024)
Aim. To collect data on the patient phenotype at the highest risk of developing albuminuria, to assess the prevalence of albuminuria in the identified phenotypes, and to collect data on the characteristics, prescribed therapy, and comorbidities of patients with and without identified albuminuria.Materials and methods. Data on presence or absence of albuminuria are collected in this register of real clinical practice instantaneously. All patients seeking medical attention are screened for the presence and extent of albuminuria. All data are collected in anonymized form and entered into an electronic case report form. Inclusion criteria: 1) men and women aged 40 years and older at the time of data collection; 2) the possibility to perform an albuminuria test using dipsticks and/or a test for microalbuminuria or urine albumin/creatinine ratio in a spot urine sample. Exclusion criteria: 1) the patient’s reluctance to participate in the registry; 2) diagnosis of CKD made before screening for the registry; 3) diagnosis of diabetes mellitus type 1 or 2 made before screening for the registry; 4) pregnancy; 5) long distance running or very heavy physical activity in the last 24 hours.Results. At the time of submission of this material, the active phase of patient recruitment for the registry with the specified power has been ongoing. Based on the expected recruitment rate at 45–50 sites, the registry is expected to include data from 12,000–15,000 patients. If fewer than 12,000 patients are recruited and the estimated recruitment rate for the registry is insufficient, the number of study sites or the screening period may be extended.Conclusion. Despite the established prognostic significance of the data on AU, the test is prescribed in routine practice to individuals at risk of developing CKD or to patients with an established nephrological disorder. A local registry that combines diverse patient populations, namely patients not only from established CKD risk groups but also patients with a dipstick test for AU, is of scientific and practical interest and can be used in the development of national clinical guidelines and educational materials and used in clinical practice.